Pengaruh Ukuran Perusahaan, Net Profit Margin, dan Total Asset Turn Over terhadap Pertumbuhan Laba - Arfandi Razak; Yoyoh Guritno; Andi Manggala Putra (Penerbit Goodwood, 2021)
Purpose: The purpose of this study is to determine the effect of company size, net profit margin, and total asset turnover on profit growth in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. Research Methodology: This type of research is a quantitative research that uses secondary data in the form of annual reports. This observation used a sample of 105 companies in the manufacturing sector. The technique for analyzing the data in this study used multiple linear regression, classical assumption test, and partial hypothesis test (t-test) with data processing using the help of the STATA v.16 application. Result: Based on the results of data analysis, it can be concluded that firm size has no effect on profit growth, and total asset turn over has a positive effect on profit growth, total asset turn over has no effect on profit growth. Limitation: The limitations of this study are some companies are late in reporting their financial statements, the study only focuses on the manufacturing sector, and the limitations of the variables used. Contribution: This research is expected to contribute for investors and companies to find out the factors that influence profit growth.